Urban microclimate and its impact on built environment – A review - Yang, Senwen; Wang, Liangzhu (Leon); Stathopoulos, Ted; Marey, Ahmed Moustafa (Building and environment, 2023)
Increasing urbanization and population growth have brought attention to urban microclimates in recent years. The study on urban microclimate and its impact on the built environment is gaining momentum. A growing number of researchers have examined the relationship between human activity and the immediate surroundings to reduce adverse impacts on the environment and climate. This paper presents the latest progress in urban microclimate research on urban wind and thermal environment, covering traditional methods, including field measurements, wind tunnel modeling, and CFD simulations, as well as emerging methods, such as artificial intelligence or data-driven models. Among the publications reviewed, the topics include isothermal scenarios that neglected thermal aspects (e.g., urban wind energy, wind comfort), as well as thermal scenarios (e.g., urban heat islands and outdoor thermal comfort). In the review, it was found that CFD has been widely applied due to its well-developed nature. In addition to field measurements, new techniques (such as satellite and thermal imaging) provide valuable validation data for CFD and training data for artificial intelligence applications. In isothermal scenarios, wind tunnel modeling has been successfully applied. However, thermal scenarios present significant challenges. In addition, urban data-driven models have emerged with promising results, but systematic investigations have been limited. In this paper, we identify future research needs for urban microclimates based on an overview of recent progress. •563 publications on urban microclimate from 2010 to 2020 were reviewed.•Research on urban microclimate increased fivefold over the past decade.•Numerical simulation is the most common approach, and data-driven models become promising.•Past findings, existing challenges, and future research needs are presented.